Milk production of pseudopregnant does - Szendrő, Zsolt; Matics, Zsolt; Gyarmati, Tünde; Theau-Clément, Michèle; Princz, Zoltán; Biróné Németh, Edit; Radnai, István; Nagy, István (Acta Agraria Kaposváriensis, 2011)
The aim of the experiment was to examine the milk production and milk composition of presumably pseudopregnant does. In experiment 1 the milk production of regular nursing multiparous (MRN) and induced to ovulation nulliparous (NIO) (n=15) and multiparous (MIO) (n=20) does injected with GnRH (15 Î¼g per animal) at 16.5 weeks of age or 11 days after parturition was examined. Compared to the MRN does NIO and MIO groups produced milk equal to 21 and 35% of the MRN does’ production. In experiment 2 primiparous and multiparous pregnant, regular nursing (PRN and MRN) /RN/ does and two groups of presumably pseudopregnant nulliparous and multiparous does: nonpregnant /PNP and MNP/ and induced to ovulation /NIO and MIO/) were examined. The milk production of the PRN and MIO does reached 70 and 58% of the MRN does’ production level (226 g milk/day). The average milk production of the MNP group was 75g but some does produced substantially higher or lower milk yield than average. The milk production of the PNP and NIO does was low. The milk composition of regular nursing does was similar to the groups of presumably pseudopregnant does. It was concluded that the MNP pseudopregnant does could be utilized as foster does.
Keywords: rabbits; pseudopregnant; milk production; milk composition